(untitled) (Communications in Computational Physics, 2018)
On Barabási-Albert networks with z neighbours selected by each added site, the Ising model was seen to show a spontaneous magnetisation. This spontaneous magnetisation was found below a critical temperature which increases logarithmically with system size. On these networks the majority-vote model with noise is now studied through Monte Carlo simulations. However, in this model, the order-disorder phase transition of the order parameter is well defined in this system and this was not found to increase logarithmically with system size. We calculate the value of the critical noise parameter qc for several values of connectivity z of the undirected Barabási-Albert network. The critical exponentes β/ν, γ/ν and 1/ν were also calculated for several values of z.